Cultural Meanings, Spiritual Adaptation, and Communal Resilience Following Spousal Loss Among Older Adults: An Ethnographic Study - Ariyanti, Sri; Jiu, Cau Kim; Anggarawati, Tuti; Pertiwi, Gracia Herni; Sastrini, Yovita Erin (Journal of Applied Nursing and Health, 2026)
Background: Spousal loss represents a significant life transition in later life, often influencing psychological well-being, social functioning, and personal identity. In rural Indonesian communities, bereavement is embedded within sociocultural contexts where spiritual beliefs, family obligations, and communal caregiving traditions shape how older adults experience and respond to loss. Despite growing attention to bereavement among older populations, ethnographic evidence examining culturally grounded adaptation processes in rural Indonesian settings remains limited. This study aimed to explore the cultural meanings of spousal loss and the adaptation experiences of older adults residing in rural Indonesian communities. Methods: A qualitative ethnographic design guided by Spradley’s ethnographic tradition was employed. Eighteen older adults who had experienced spousal loss were recruited through purposive sampling. Data were collected during six months of field engagement using in-depth interviews, participant observation, field notes, and focus group discussions. Data were analyzed through thematic ethnographic analysis to identify culturally embedded patterns of meaning and adaptation. Results: Four interconnected themes emerged: spiritual acceptance of spousal loss, cultural values fostering resilience, communal caregiving practices, and loneliness after bereavement. Informants understood spousal loss not only as an emotional experience but also as a sociocultural and spiritual transition. Adaptation was facilitated through religious practices, family responsibilities, collective caregiving traditions, and community support, while loneliness and the loss of emotional companionship remained enduring challenges. Conclusion: Adaptation to spousal loss among older adults is deeply influenced by cultural values, spirituality, and community relationships. These findings contribute to a deeper understanding of culturally embedded bereavement processes and provide a foundation for future cross-cultural and intervention-based research addressing grief and adaptation in later life.